Nitrite sensing: Utilizing titanium dioxide and copper-doped titanium dioxide in electrochemical detection - Htet, Thura Lin; Prasitkhetkit, Natthanon; Asava-arunota, Manasbodin; Panomsuwan, Gasidit; Techapiesancharoenkij, Ratchatee; Pewnim, Naray; Jongprateep, Oratai (Agriculture and Natural Resources, 2024)
Importance of the work: This study is essential for food safety. Detecting nitrite with electrochemical sensing prevents bacterial growth and mitigates health risks. Objectives: To synthesize titanium dioxide (TiO2)/copper (Cu)-doped TiO2 through solution combustion and explore their nitrite detection via electrochemical sensors. Materials and Methods: TiO2 and Cu-doped TiO2 fine particles were synthesized via a solution combustion process, followed by calcination and hydrothermal treatments with multi-walled carbon nanotubes (MWCNTs). The resulting composite was drop-cast onto glassy carbon electrodes and its sensing performance was assessed using cyclic voltammetry. Results: The solution combustion method reduced the Cu-doped and undoped TiO2 particles from 500 nm to less than 280 nm. Combined with MWCNTs, these particles were applied as sensing materials in electrodes. Electrochemical tests showed oxidation at 0.55 V and reduction near -0.85 V in a nitrite solution. The Cu-doped TiO2/MWCNTs had stronger oxidation and reduction peaks compared to the TiO2/MWCNTs. Sensitivity analyses indicated heightened peak intensity with rising nitrite levels and excellent linearity, suggesting their high potential for nitrite detection. Main finding: The effectiveness of solution combustion in refining TiO2 and Cu-doped TiO2 particles, combined with MWCNTs, enhanced electrode electrocatalysis. This process produced superior materials for effective nitrite detection in environmental and food safety monitoring.